THE EFFECT OF SELF EFFICACY AND SOCIAL SUPPORT ON STUDENTS’ EMPLOYABILITY FACING WORKFORCE CHALLENGES - Nazwa Amelia Rangkuti; Faisal Umardani Hasibuan; Tri Inda Fadhila Rahma (Jurnal Interprof, 2026)
The fast paced transformation of the modern job market demands that university students possess not only academic knowledge but also mental and social preparedness. Despite this, a considerable number of prospective graduates still experience anxiety regarding their transition into professional roles. Consequently, this research investigates how self-efficacy and social support impact the employability of students at the Faculty of Islamic Economics and Business, State Islamic University of North Sumatra. Utilizing a quantitative causal design, the study selected 98 respondents via purposive sampling. Empirical data gathered through a Likert-scale survey were processed using multiple linear regression analysis via SPSS. The findings reveal that both self-efficacy and social support exert a positive and statistically significant influence on students' employability, either individually or concurrently. Elevated self-confidence enables students to better navigate recruitment processes, while adequate support from family, peers, and the academic community fosters motivation and clarifies career trajectories. Ultimately, this study highlights that achieving employability goes beyond mere academic excellence, it fundamentally relies on individual psychological resilience and a nurturing social ecosystem.